IPEM topical report 1: guidance on implementing flattening filter free (FFF) radiotherapy. (7th November 2016) - Budgell, Geoff; Brown, Kirstie; Cashmore, Jason; Duane, Simon; Frame, John; Hardy, Mark; Paynter, David; Thomas, Russell
Abstract: Flattening filter free (FFF) beams are now commonly available with new standard linear accelerators. These beams have recognised clinical advantages in certain circumstances, most notably the reduced beam-on times for high dose per fraction stereotactic treatments. Therefore FFF techniques are quickly being introduced into clinical use. The purpose of this report is to provide practical implementation advice and references for centres implementing FFF beams clinically. In particular UK-specific guidance is given for reference dosimetry and radiation protection.